If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6v + -10 = 2v + 2 Reorder the terms: -10 + 6v = 2v + 2 Reorder the terms: -10 + 6v = 2 + 2v Solving -10 + 6v = 2 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. -10 + 6v + -2v = 2 + 2v + -2v Combine like terms: 6v + -2v = 4v -10 + 4v = 2 + 2v + -2v Combine like terms: 2v + -2v = 0 -10 + 4v = 2 + 0 -10 + 4v = 2 Add '10' to each side of the equation. -10 + 10 + 4v = 2 + 10 Combine like terms: -10 + 10 = 0 0 + 4v = 2 + 10 4v = 2 + 10 Combine like terms: 2 + 10 = 12 4v = 12 Divide each side by '4'. v = 3 Simplifying v = 3
| 230x-25=440 | | 7x-7=x+29 | | 25x-230=440 | | c=38.51+0.50x | | 5x+2=-4(x-3) | | 6b+8a=9 | | 180=(20y-10)+2x | | 25x+330=440 | | 7+2.5h=19-4x | | 14=4h-6 | | 3(d-1)=12 | | 230x+25=440 | | 195=56-v | | -16x--2=46 | | 5x+86=11x-10 | | r^2=9r-18 | | 10=2+2j | | -13+10x=-63 | | 7+2.5x=19-4x | | 25x+230.00=440.00 | | 31=3(w+7)-8w | | 4x+4=-6x+24 | | 6x+5+67=180 | | 7(3y+2)=-2 | | -12=-x+3x | | 8(5x+10)=40x-5 | | 24+8(c-3)=7c+5 | | 0.02x-0.2=4 | | 5(1+36)=-43+9b | | xy-3x-y=3 | | 5(x+6)=4(3-2x) | | f(x)=2x^2+11x |